Characterization of microstructure and mechanical properties of Super Ni 718 alloy and AISI 316L dissimilar weldments. Issue 24 (14th November 2014) - Prabaharan, P.; Devendranath Ramkumar, K.; Arivazhagan, N.
Abstract